Missiological approach to Migration and Mission in Pentecostalism: a Pneumatological Missional Imagination - Kgatle, Mookgo Solomon (Ecclesial Futures, 2024)
While much has been written on the intersections of migration and mission, little has been developed regarding theoretical frameworks for approaching the subject from the discipline of missiology. This calls for the development of a framework that will assist in the missiological approach to migration and mission. However, there is a need for the recognition of the current missiological approaches to migration and mission to identify the existing gaps such as relevancy to Pentecostalism. To fill this gap, this article brings together three theories of pneumatological imagination, missiological spirit, and missional imagination to develop a pneumatological missional imagination. The findings are, that a pneumatological missional imagination is relevant for dealing with some of the challenges in migration and mission in Pentecostalism such as the inability to minister relevantly to the host countries, cultural differences, and orientation to the mission of God. These challenges are outlined by using the Apostolic Faith Mission Ministry International in the United Kingdom (AFMIMUK) as a case study. The pneumatological missional imagination is relevant for witnessing to others, speaking foreign languages, and orientation to the mission of God. therefore, a pneumatological missional imagination is relevant as a missiological approach to the intersections of migration and mission in Pentecostalism.